Political Image of the Regional Leader on Instagram - D. I. Kaminchenko (Управленческое консультирование)
The article is devoted to the study of the features of modern political communication in the context of society networkization. The interaction of a regional political leader and society in the sign-symbolic space of political communication is considered.The purpose of this paper is to identify the main image-role semantic constructs, which are reflected in the messages of the head of the constituent entity of the Russian Federation, posted by him on the popular Internet platform for social media Instagram. In addition to establishing the most actively used semantic image-role constructs, the research determines the degree of it`s popularity and the level of it`s approval among the audience of this Internet platform.The qualitative and quantitative type of content analysis was chosen as the main applied research method. In addition to it, a comparative analysis method is used. The conceptual basis of the research is formed by the theory of the information society, as well as the concepts of “network image”, “digitalization policy” and “network identity”.According to the results of the conducted content analysis, it was found that more often than others in the messages posted on the studied official Internet page of the political leader in Instagram, such an image-role construct as an “organizer” is presented. This corresponds to the type of leadership characteristic of this political leader. Among the entries that aroused a relatively increased attention of the audience of the Internet platform, there are messages where a number of image-role constructs are presented, including: “crisis manager”, “organizer”, “team player”, “builder”, “open leader, hearing society” and “business executive”. Such a uniform distribution of the audience’s interest in it`s functional and semantic constructs may be explained by the fact that the head of the region is actively paying attention to each of the designated thematic areas.The highest level of approval from the audience of the Internet platform was received by the messages, which reflected such image-role constructs as “family man” and “leader looking to the future”. Considering the relatively inactive use of the designated semantic constructs by the head of the region in the messages posted on his official Instagram page, it is noted that an increase in the number of messages, which would reflect these image-role constructs, may enhance the leader’s positive image and, as a result, the level of his support in society.